Prevalence of Systemic Arterial Hypertension Diagnosed, Undiagnosed, and Uncontrolled in Elderly Population: SABE Study - Isabela Martins Oliveira; Yeda Aparecida de Oliveira Duarte; Dirce Maria Trevisan Zanetta (Journal of Aging Research)
Systemic arterial hypertension is the most prevalent chronic noncommunicable disease among older people. This study aimed to estimate the prevalence of hypertension in the elderly and to analyze factors associated with diagnosed, undiagnosed, and uncontrolled hypertension. This is a cross-sectional study of data from the SABE study—Health, Well-Being, and Aging Survey—a multiple-cohort study, obtained in 2010, composed of a probabilistic sample representative of the population of the São Paulo city aged ≥60 years. Hypertension was self‐reported or defined by increased blood pressure. Multinomial regression assessed factors associated with diagnosis and lack of diagnosis of hypertension (reference: no hypertension), and logistic regression assessed factors associated with uncontrolled hypertension (reference: controlled). The prevalence of hypertension was 79.5%, and in 51% of individuals with the condition, hypertension was uncontrolled. Undiagnosed hypertension was associated with nonwhite skin color (OR: 1.89, CI: 1.11–3.19), being uninsured (OR: 1.77, CI: 1.04–3.03), overweight (OR: 2.38, CI: 1.09–5.19), higher education (OR: 0.46, CI: 0.22–1.94), and ≥1 chronic disease (OR: 0.28; CI: 0.13–0.58). Diagnosed hypertension was associated with age between 70 and 79 years (OR: 2.02, CI: 1.34–3.05), age ≥80 (OR: 2.73, CI: 1.72–4.31), nonwhite skin color (OR: 1.48, CI: 1.01–2.18), being uninsured (OR: 1.70, CI: 1.18–2.47), at least one medical consultation in the last year (OR: 1.86, CI: 1.06–3.25), obesity (OR: 2.50, CI: 1.61–3.88), and ≥1 chronic disease (OR: 2.81, CI: 1.94–4.08). Among those with hypertension, being uncontrolled was associated with widowhood (OR: 1.73, CI: 1.23–2.43), being uninsured (OR: 1.38, CI: 1.02–1.87), and female gender (OR: 0.61, CI: 0.43–0.87). The prevalence of hypertension was high in this population, and its diagnosis and control were associated with socioeconomic, demographic, and healthcare access factors.